Acylcarnitines activate proinflammatory signaling pathways - Rutkowsky, Jennifer M; Knotts, Trina A; Ono-Moore, Kikumi D; McCoin, Colin S; Huang, Shurong; Schneider, Dina; Singh, Shamsher; Adams, Sean H; Hwang, Daniel H (American journal of physiology: endocrinology and metabolism, 2014)
Incomplete β-oxidation of fatty acids in mitochondria is a feature of insulin resistance and type 2 diabetes mellitus (T2DM). Previous studies revealed that plasma concentrations of medium- and long-chain acylcarnitines (by-products of incomplete β-oxidation) are elevated in T2DM and insulin resistance. In a previous study, we reported that mixed D,L isomers of C12- or C14-carnitine induced an NF-κB-luciferase reporter gene in RAW 264.7 cells, suggesting potential activation of proinflammatory pathways. Here, we determined whether the physiologically relevant L-acylcarnitines activate classical proinflammatory signaling pathways and if these outcomes involve pattern recognition receptor (PRR)-associated pathways. Acylcarnitines induced the expression of cyclooxygenase-2 in a chain length-dependent manner in RAW 264.7 cells. L-C14 carnitine (5-25 μM), used as a representative acylcarnitine, stimulated the expression and secretion of proinflammatory cytokines in a dose-dependent manner. Furthermore, L-C14 carnitine induced phosphorylation of JNK and ERK, common downstream components of many proinflammatory signaling pathways including PRRs. Knockdown of MyD88, a key cofactor in PRR signaling and inflammation, blunted the proinflammatory effects of acylcarnitine. While these results point to potential involvement of PRRs, L-C14 carnitine promoted IL-8 secretion from human epithelial cells (HCT-116) lacking Toll-like receptors (TLR)2 and -4, and did not activate reporter constructs in TLR overexpression cell models. Thus, acylcarnitines have the potential to activate inflammation, but the specific molecular and tissue target(s) involved remain to be identified.